Characterization of a monoclonal antibody to L1210 leukaemia. - Testorelli, C. (Nature Publishing Group, 1982)
A mouse of monoclonal cell line (L1) was produced by fusing the mouse myeloma P3X63/Ag8 with CD2F1 spleen cells immunized with a highly immunogenic subline of L1210 leukaemia (L1210/DTIC). A very few positive clones (1%) were isolated and one of these was chosen for detailed study. The monoclonal antibody L1 is an IgM immunoglobulin strongly reacting in a complement-dependent cytotoxicity assay against L1210/Cr leukaemia and its more or less immunogenic sublines. The specificity of the L1 antibody against L1210 leukaemia was studied by extensive screening with normal adult and foetal tissues, lymphoid tissues from several independent strains and a panel of the most common experimental tumours, to all of which it was unreactive. Attempts at immunotherapy were carried out in DBA/2 mice challenged with L1210 leukaemia and treated with L1 (ascites) and complement. Although the in vitro cytotoxic titre of ascites fluid from mice bearing hybridoma was very high (10(-7)), no therapeutic effect was obtained in vivo.